If A = 3x² - 4x + 1, B = 5x² + 3x - 8 and C = 4x² - 7x + 3, then find (A + B) - C
Solution:
Given, A = 3x² - 4x + 1, B = 5x² + 3x - 8 and C = 4x² - 7x + 3
We have to find (A + B) - C
A + B = 3x² - 4x + 1 + (5x² + 3x - 8)
= 3x² - 4x + 1 + 5x² + 3x - 8
By combining like terms,
= 3x² + 5x² - 4x + 3x + 1 - 8
= (3 + 5)x² + (-4 + 3)x + (1 - 8)
= 8x² + (-1)x - 7
A + B = 8x² - x - 7
(A + B) - C = 8x² - x - 7 - (4x² - 7x + 3)
= 8x² - x - 7 - 4x² + 7x - 3
By combining like terms,
= 8x² - 4x² - x + 7x - 7 - 3
By distributive property,
= (8 - 4)x² + (-1 + 7)x + (-7 - 3)
= (4)x² + (6)x + (-10)
Therefore, (A + B) - C = 4x² + 6x - 10
✦ Try This: If A = x² + x + 1, B = 4x² - 3x + 2 and C = x² - 4x + 6, then find (A + B) - C
☛ Also Check: NCERT Solutions for Class 7 Maths Chapter 12
NCERT Exemplar Class 7 Maths Chapter 10 Problem 68 (i)
If A = 3x² - 4x + 1, B = 5x² + 3x - 8 and C = 4x² - 7x + 3, then find (A + B) - C
Summary:
If A = 3x² - 4x + 1, B = 5x² + 3x - 8 and C = 4x² - 7x + 3, then (A + B) - C is 4x² + 6x - 10
☛ Related Questions:
visual curriculum